PENGARUH ASIMETRI INFORMASI DAN KESESUAIAN KOMPENSASI SERTA KETAATAN ATURAN AKUNTANSI TERHADAP KECURANGAN AKUNTANSI (Studi Empiris pada OPD Kabupaten Tanah Datar) - Aysha Aulia Amril; Siska Yulia Defitri; Nidia Anggreni Das (OPTIMAL Jurnal Ekonomi dan Manajemen, 2022)
This study aims to examine the effect of information asymmetry, Compensastion Suitability, and Complience with Accounting Rules on accounting fraud (empirical study on OPD Tanah Datar Regency). While the research sample is the Head, Treasurer, and Head of the Finance Subdivision in the OPD (Regional Apparatus Organization) of Tanah Datar Regency, totaling 117 respondents. The type of data used is primary data. The sample technique used is total sampling by distributing questionnaires.The result show that Information Asymmetry (X1) has an effect on Accounting Fraud (Y). This result is evidenced by the significance value of t of 0,000 <0,05. While Compensation Suitability (X2) has an effect on Accounting Fraud (Y). This result is avidenced by a significance value of 0,000< 0,05. And Compliance with Accounting Rules (X3) has an effect on Accounting Fraud (Y). This result is evidenced by the significance value of F of 0,000 < 0,05.